Influence of antioxidants and salinity stress on seedling parameters of some rice cultivars - A.E. Sharief, A. A. Kandil; EL-Fatah, Fatma M. Abd (Journal of Plant Stress Physiology, 2019)
An investigation was conducted to study the response of antioxidants seed priming on rice cultivars and their effect on germination under salinity levels. The result indicated that the highest in shoot height (cm), root height (cm), seedling vigor index, and other related parameters, relative dry weight% were produced from Sakha 106 cultivar. The lowest seedling height reduction % was produced from Sakha 106 cultivar. An enhancement in salt concentration resulted a reduction in all studied parameters except seedling height reduction %. The results indicated the highest shoot height (cm), root height (cm),seedling vigor index, shoot fresh and dry weight (mg), root fresh and dry weight (mg), relative dry weight% and seedling height reduction % from which soaking, as pretreatment, in Humic acid at 500ppm. The interactions between cultivars, salinity concentration and antioxidants were insignificant on some traits. It could be concluded that to improve seedling parameters of rice cultivars under salinity stress; it could be recommended that soaking Sakha 106 cultivar seed in Humic acid at 500 ppm for 24 h. It can be used in breeding program to boost production in Egyptian territory.